[Image 31] - Smith, Captain Sir William [?ob. 1732] (My University, 1806)
Captain Sir William Smith was in the Royal Engineers.
Original drawings and paintings of Ireland and Scotland, vol 1
View of Greencastle as seen from the green before [indecipherable] looking down Lough Foyle prior to the new works there by Sir Wm Smith 1806.
Keywords: Greencastle; Fortification; Architectural drawings; Ireland -- Antiquities -- Pictorial works; Donegal (Ireland : County) -- Pictorial works; Inishowen Peninsula (Ireland) -- Pictorial works; Lough Foyle (Northern Ireland and Ireland); Landscapes (Representations) 1800-1810